Servicescape, positive affect, satisfaction and behavioral intentions: The moderating role of familiarity - Park, Jeong-Yeol; Back, Robin M.; Bufquin, Diego; Shapoval, Valeriya (International journal of hospitality management, 2019)
•Substantive and communicative servicescape increases positive affect, which improves satisfaction and behavioral intentions.•The influence of substantive servicescape on positive affect is greater than the influence of communicative servicescape.•Brand familiarity negatively moderates the relationship between substantive servicescape and positive affect.•The effect of substantive servicescape on positive affect is greater for participants with low brand familiarity.•Positive affect fully mediates the relationship between substantive and communicative servicescape and satisfaction. This study is the first to assess the relationships between substantive and communicative servicescape, positive affect, satisfaction, and behavioral intentions in a highly substantively staged hotel setting, as well as the moderating effects of brand and architectural familiarity. One hundred fifty online responses were obtained from guests who stayed at a hotel in the Rioja region of Spain, designed by world-renowned architect Frank Gehry, famous for creating architectural landmarks that disrupt the local landscape. Data were analyzed utilizing Partial Least Squares – Structural Equation Modeling (PLS-SEM). Findings show that both substantive and communicative servicescape positively influence hotel customers’ positive affect, which has a positive impact on satisfaction, and which in turn significantly increases behavioral intentions. Brand familiarity moderates the relationship between substantive servicescape and positive affect, with the influence being greater for participants with low familiarity than for those with high familiarity. Theoretical and practical implications are discussed in detail.